Kajian Isoterm Adsorpsi Linear Alkilbenzena Sulfonate (LAS) dalam Limbah Cair Detergen Menggunakan Biosorben Ampas Kopi dan Ampas Kelapa - Mimin Septiani; Zakiyah Darajat; Muhammad Arham Yunus; Maria Assumpta Nogo Ole; Zuhrotul Fikri Ilma (Eksergi, 2023)
One of the efforts to minimize the impact of detergent waste pollution is by adsorption using coffee dregs and coconut dregs adsorbents. The purpose of this study was to determine the optimum mass of coffee grounds and coconut pulp as adsorbents, to compare the effectiveness of their absorption in decreasing levels of Linear Alkyl Benzene Sulfonate, and to study their adsorption isotherm models. This research was conducted in batches with variations in the mass of each adsorbent, namely 1 gram, 2 grams, 3 grams, 4 grams and 5 grams. This research was conducted in batches with variations in the mass of each adsorbent, namely 1 gram, 2 grams, 3 grams, 4 grams and 5 grams. The detergent waste samples were contacted with the adsorbent for 30 minutes and then the absorption capacity was tested using the Methylene Blue test method. The results showed that the optimum absorption of LAS content from coffee grounds and coconut pulp adsorbents occurred at a mass of 2 grams with the greatest increase in absorption efficiency index Coconut dregs adsorbent is more effective than coffee dregs because it can absorb up to 37%, while coffee dregs are only 10% with the same adsorbent mass of 5 grams. The adsorption isotherm model of the 2 types of adsorbents refers to the Langmuir equilibrium with R2 values for coffee grounds 0.8651 and coconut pulp 0.9868.